Quantitative Flow Ratio Identifies Nonculprit Coronary Lesions Requiring Revascularization in Patients With ST-Segment–Elevation Myocardial Infarction and Multivessel Disease. (February 2018) - Spitaleri, Giosafat; Tebaldi, Matteo; Biscaglia, Simone; Westra, Jelmer; Brugaletta, Salvatore; Erriquez, Andrea; Passarini, Giulia; Brieda, Alessandro; Leone, Antonio Maria; Picchi, Andrea; Ielasi, Alfonso; Di Girolamo, Domenico; et al.
Abstract : Background—: The nonculprit lesion (NCL) management in ST-segment–elevation myocardial infarction patients with multivessel disease is debated. We sought to assess whether quantitative flow ratio (QFR), a noninvasive tool to identify potentially flow-limiting lesions, may be reliable in this scenario. Methods and Results—: The present proof-of-concept study is based on a 3-step process: (1) identification of the QFR reproducibility in NCLs assessment (cohort A, n=31); (2) prospective validation of QFR diagnostic accuracy in respect to fractional flow reserve (cohort B, n=45); and (3) investigation of long-term clinical outcomes of NCLs stratified according to QFR (cohort C, n=110). A blinded core laboratory computed QFR values for all NCLs. Cohort A showed a good correlation and agreement between QFR values at index (acute) and at staged (subacute, 3–4 days later) procedures ( r =0.98; 95% confidence interval, 0.96–0.99; mean difference, 0.004 [−0.027 to 0.34]). The inter-rater agreement was κ=0.9. In cohort B, fractional flow reserve and QFR identified 16 (33%) and 17 (35%) NCLs potentially flow limiting. Sensitivity, specificity, negative, and positive predictive values were 88%, 97%, 94%, and 94%. The area under the receiver operating characteristics curve was 0.96 (95% confidence interval, 0.89–0.99). Finally, in cohort C, we identified 110 ST-segment–elevation myocardial infarction patients where at least 1 NCL was left untreated. Patients with NCLs showing a QFR value ⩽0.80 were at higher risk of adverse events (hazard ratio, 2.3; 95% confidence interval, 1.2–4.5; P =0.01). Conclusions—: In a limited and selected study population, our study showed that QFR computation may be a safe and reliable tool to guide coronary revascularization of NCLs in ST-segment–elevation myocardial infarction patients. Abstract : Supplemental Digital Content is available in the text.